Design and Development of a Class of Rotorcraft-Based UAV. (15th February 2013) - Kim, Gyou Beom; Nguyen, Trung Kien; Budiyono, Agus; Park, Jung Keun; Yoon, Kwang Joon; Shin, Jinok
We discuss the development of a mini-quadrotor system and coaxial quadrotor system for indoor and outdoor applications. The attitude control system consists of a stability augmentation system and a modern control approach. To perform an experimental flight test, a PID controller is used to validate our aerodynamic modelling and basic electronics hardware is developed in a simple configuration. We use a low-cost 100 Hz AHRS for inertial sensing, infrared (IR) sensors for horizontal ranging, an ultrasonic sensor for ground ranging and an AVR microcontroller for the flight control computer. A ground control system is developed for the monitoring and gathering of flight data. Based on the modelling and simulation data of the mini-quadrotor system, a flight test is performed and automatic hovering ability is implemented. A collision detection system is one of the important parts of an indoor and outdoor flight test. To overcome the payload limitation of the mini-quadrotor system, we design a coaxial quadrotor system and we use a Kinect sensor as the collision detect sensor. Kinect sensors give 3D depth information and the collision detection system uses that information.